2013
DOI: 10.1177/1059601113488939
|View full text |Cite
|
Sign up to set email alerts
|

What Trust Matters When

Abstract: While trusting coworker relationships are conducive to knowledge transfer, distinct types of trust and the contextual conditions under which they are most effective have received limited empirical attention. In this article, we distinguish between professional and personal trust, and hypothesize that their relative knowledge transfer advantage may vary as a function of the duration of the receiver-source relationship. Using survey data from 135 knowledge receivers reporting on their relationships with their kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 108 publications
1
6
1
Order By: Relevance
“…This study contributes to the growing literature on public trust and policy compliance in several ways. Firstly, we found that public trust was positively related to the compliance of respondents practicing personal protective measures and reaffirmed that public trust in the government determines the tendency of policy compliance [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 19 ]. In Thailand, after the government established the Center for COVID-19 Situation Administration (CCSA) as a special task force responding to the pandemic when a strict lockdown policy was implemented in late March, immediate three-month financial compensation to those affected by the lockdown policy and vulnerable groups was also applied.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study contributes to the growing literature on public trust and policy compliance in several ways. Firstly, we found that public trust was positively related to the compliance of respondents practicing personal protective measures and reaffirmed that public trust in the government determines the tendency of policy compliance [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 19 ]. In Thailand, after the government established the Center for COVID-19 Situation Administration (CCSA) as a special task force responding to the pandemic when a strict lockdown policy was implemented in late March, immediate three-month financial compensation to those affected by the lockdown policy and vulnerable groups was also applied.…”
Section: Discussionsupporting
confidence: 56%
“…Literature suggested that professional trust was regarded as another crucial determinant for policy compliance. Professional trust can be defined by the willingness of a person to rely on the skills and abilities of experts [ 19 ]. It has been found that health agencies enhance public trust and positively influence people’s willingness to adopt recommended behavior [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…When co‐worker trust is high, helping behaviors are more common; employees are more likely to exchange resources (e.g., knowledge; Alexopoulos & Buckley, 2013), to view criticism by co‐workers as valuable feedback rather than personal attack, and to make effective team decisions (Arnett & Wittmann, 2014; Costa, Fulmer, & Anderson, 2018; Kim, Dirks, & Cooper, 2009; Nienaber, Holtgrave, & Romeike, 2018). When organizational trust is high, employees are more likely to develop a sense of identification with and belonging to the organization, to voice their concerns rather than withdraw from the organization or engage in negative behaviors, and to perceive the organization as authentic (Polat, 2013; Schoorman, Mayer, & Davis, 2007).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Relationship length incorporates aspects having to do with the development and maintenance of interpersonal relationships and was found to be a key indicator affecting the nature of relationships between parties in various contexts (e.g., mentor–mentee and buyer–seller) as well as the outcomes associated with such relationships (Claycomb & Frankwick, 2004; Holtgrave, Nienaber, & Ferreira, 2017). For example, co‐workers engaged in relationships of longer duration were more likely to share knowledge (Alexopoulos & Buckley, 2013), and mentees showed better academic performance later (than earlier) in the mentorship process (Grossman et al, 2012). Similarly, in marketing research, Dagger, Danaher, and Gibbs (2009) observed a relationship‐maturity effect, in which customer‐reported relationship strength was higher for longer duration relationships.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Relevant information is available to all partners within inter-organizations, including public and private information (Chen et al 2011;Uzzi, Lancaster 2003). However, extremely open private information shared with other partners with whom there is little shared experience is likely to lead to negative consequences unless it is clear that the principle of information sharing is understandable to all partners (Alexopoulos, Buckley 2013).…”
Section: Information Availability (B1)mentioning
confidence: 99%